Examining the utilization of web-based discussion tools in teaching and learning organic chemistry in selected Rwandan secondary schools - Aloys Iyamuremye; Innocent Twagilimana; Francois Niyongabo Niyonzima (Heliyon)
In recent years, the teaching and learning of organic chemistry have frequently faced challenges due to limited student engagement and participation. Consequently, there is a growing demand for innovative teaching methods to tackle these issues. In this context, web-based discussions have emerged as a hopeful approach to enhance students' engagement and foster critical thinking skills. Therefore, the present study investigated the level of adoption of web-based discussion tools in teaching organic chemistry in Rwandan secondary schools for addressing the challenge of limited student engagement and participation. A quantitative research approach relying on a survey questionnaire was used to collect data from 133 secondary school chemistry teachers in Kamonyi and Gasabo districts. The findings indicate that 78 % of teachers do not use web-based discussion tools, while 22 % have integrated these tools into their teaching. The preferred platforms among users include WhatsApp groups, Google Docs, and Google Classroom. Additionally, the study highlights key organic chemistry topics such as alkanes, polymers, polymerization, and alcohol that can be effectively taught through these tools. Statistical analysis using ANCOVA did not show significant differences in the use of web-based discussion tools based on factors like school location, teachers’ age, school ownership, and teaching experience, with p-values of 0.817, 0.234, 0.380, and 0.051, respectively. However, the borderline significance related to teaching experience (p = 0.051) suggests a potential trend. A significant difference was observed in terms of gender, with male teachers more likely to use these tools (p = 0.015). The study offers valuable insights into the factors influencing the adoption of web-based discussion tools in Rwanda, offering useful guidance for educators and curriculum developers to create more engaging and inclusive chemistry lessons.